Implementasi Kebijakan Perluasan Kesempatan Kerja Bagi Fresh Graduate di Masa Sebelum dan Saat Pandemi Covid-19 di Kota Tangerang - Ratu Khairun Azzahra; Isnadya Muharromah; Annemarie Fatimah Fauziyah; Yuswita Safa Maharani; Natashia Salsabila; Nur Ficky Fauziyah; Irvan Arif Kurniawan (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
The open unemployment rate and the low number of jobs have become the main concerns in labor issues and the targets of the sustainable development goals agenda in Tangerang City. The Covid-19 pandemic also has an impact on the employment sector, namely limited job vacancies and limited work experience, which also affects fresh graduates. This study aims to describe how the Implementation of the Employment Opportunities Expansion Policy in Tangerang City before and during the Covid-19 pandemic is seen from several programs that have been issued before and during the pandemic. The method used in this research is qualitative using interview and documentation techniques. This research uses the Dennis A. Rondinelli and G. Shabbir Cheema Implementation Model, which is a theoretical framework used to examine how decentralized government initiatives are implemented. The environment, notions of interorganizational linkages, organizational resources for program implementation, and the traits and skills of implementing agents are four variables that may have an impact on how a policy is implemented. The findings show that the program was not implemented as well as it should have been in order to improve career possibilities for Fresh Graduate both before and during the Covid-19 outbreak at the Tangerang City Manpower Office many differences were towards better services. However, there are still problems in the provisions for participants who join the program that should be improved so as not to hinder other participants. Keywords: Job opportunities, Unemployment, Fresh Graduates, Covid-19